Cohesion and Interpersonal Interaction in How to Teach English by Jeremy Harmer: A Systemic Functional Analysis - Muhammad Zahid; Seemab Jameel Ghauri; Muhammad Nadeem Anwar (Corresponding Author) (`, 2026)
This study utilizing the Systemic Functional Linguistics (SFL) aims to investigate the organization of a text (cohesion through repetition/conjunctions) and interpersonal interaction (pronouns, questions, modality, evaluation using appraisal) in one excerpt of the text of the book How to Teach English by Jeremy Harmer (1998) (pp. 68-69), a pedagogical piece on reading EFL. Based on the cohesion framework of Halliday and Matthiessen (2014) and the appraisal theory of Martin and White (2005), the analysis that is supported by highlighted paragraphs (Appendices A-D) demonstrates tight chains of lexicon used (reading, 32x; students, 18x) and conjunctive pivots (also, however) that support the progression Interpersonally, collaborative persuasion is achieved by using inclusive pronouns (we, 9x), rhetorical questions (3x), and modal gradients (must, 4x; may, 7x), and positive appraisal supports the usefulness of reading in an attitudinally positive way (good, 4x). Results indicate how Harmer skillfully crafts understandable, navigable discourse to EFL teachers and sets an example of inclusive pedagogy in debates of the 1990s. It has been discussed that cohesive texture has been found to enhance readability and that interactional rapport has been found to build rapport and this would have implications in materials design in applied linguistics. Keywords: Discourse analysis, cohesion, interpersonal interaction, ESL pedagogy, SFL